PENGARUH STRATEGI PEMBELAJARAN CRITICAL INCIDENT TERHADAP LITERASI NUMERASI SISWA - Nur Jannah Daulay (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
The examination that has been directed is named "The impact of basic occurrence systems on understudies' numeracy education in factual material in class VIII SMP N 1 Sosa Julu" with the foundation being that understudies' numeracy proficiency is still low since understudies are not yet ready to apply arithmetic to regular day to day existence - day and dissect the data showed as: outlines, tables, diagrams and charts and understudies have not had the option to decipher the consequences of the examination to reach inferences. The examination philosophy utilizes a semi trial approach with pre-test and post-test in the two classes. This depends on the models for working out the t-test, which is acquired Tcount = 7.503 and Ttable = 2.013, in light of the fact that Tcount > Ttable with 24 each example. The N-Gain test, based on the results of the calculation of N-The gain, reveals that the experimental N-Gain value for moderate criteria is 90 percent, indicating the influence of this critical incident strategy. In the interim, the N-Gain an incentive for the control class with moderate models is 80%. So it very well may be presumed that the numeracy proficiency test scores of understudies who were educated with the basic episode system were higher than those instructed with ordinary learning in class VIII SMP N 1 Sosa Julu.